Deixis Used by The English Lecturers At Muhammadiyah University Of Bengkulu - Roza Apriani; Ririn Putri Ananda (Teaching English and Language Learning English Journal, 2024)
Deixis is a phenomenon in human language that highlights the relationship between context and words. This research aims to find out the deixis used by english Lecturers at Muhammadiyah University of Bengkulu. The type of research used in this research is descriptive analysis. The instruments used are observation checklist and record. The subjects of this research were 3 English lecturers at Muhammadiyah University of Bengkulu. The results of this study show that there were 68 deixis used by the English Lecturers. Mr. Epi Wadison in semantic and pragmatic’s class used 11 times of person deixis, 4 times of time deixis, 2 time of place deixis, 5 times of discourse deixis and 1 time of social deixis. Mr. Epi Wadison in Instructional planning’s class used 14 times of person deixis, 4 times of time deixis, 2 times of place deixis, 5 times of discourse deixis and 4 times of social deixis. Mr. Wahyudi Badri in listening’s class used 3 times of person deixis, 2 times of time deixis, 2 times of discourse deixis and 2 times of social deixis. Mrs. Ririn Putri Ananda in Speaking for Debate’s class used 3 times of person deixis, 2 times of time deixis, 2 times of place deixis and 1 time of social deixis.. This research shows that Person Deixis is the most frequently used type of deixis. Keywords: Deixis, Lecturers, English deixis